Mastocytosis with small monomorphic macules. - Milano, A. (European Journal of Pediatric Dermatology, 2018)
Mastocytosis with small monomorphic elements (2) is characteristic of the adult, although rarely it can be observed in the child: in the latter it has been related to a longer duration of the disease (1). The clinical diagnosis is easier when there is a swelling of the lesions and itching. When, as in this case, the lesions are not infiltrated, the mast cells in the papillary dermis are few, as shown by the histological examination, and also the sign of Darier is not very evident, only appreciable as a transitory variation of color and palpability of the macule. The prognosis of adult cutaneous mastocytosis is good in spite of a longer duration at this age. The clinically evident bone marrow involvement is exceptional even when the marrow smear shows the presence of mast cells. A bone marrow examination should be performed when serum triptase is greater than 100 μg / mL (3).